Geohistory Analysis of South Makassar - Peter Lunt; J.T. (Han) van Gorsel (Berita Sedimentologi, 2013)
A quantitative approach to stratigraphy shows how the south Makassar Straits Basin developed, and how the major sequences of sediment were deposited. After the initial rifting of the grabens there were four major, basin changing, unconformities that strongly affected sedimentation; at about 39 Ma (later Middle Eocene), 36 Ma (early part of Late Eocene), 34 Ma (almost on the Eocene to Oligocene boundary) and about 24 Ma (almost at the Oligocene-Miocene boundary).The 39 Ma event saw accelerated rifting on the distal margins of Sundaland, in the south and southeast. The 36 Ma event is very strongly expressed in the South Makassar area and is shown by the geohistory analysis to have included basement subsiding by as much as 2 kilometres in 2 million years. The 34 Ma event led to the onset of the Berai Limestone to the west and very strongly reduced rates of deep-water sedimentation throughout the Makassar to Spermonde area. The c. 24 Ma event saw a substantial change in sedimentary conditions, with the end of condensed deep marine clastics and shallow marine Berai carbonates, and the start of a new clastic phase with high rates of sedimentation. These times of major change are all thought to be controlled by tectonism, because their magnitude exceeds rates of eustatic change, and also because their geographic expression is highly variable.The first rift phase contains important lacustrine hydrocarbon source rocks in the inland areas of Sundaland, and large deltas with coaly sources on the fringes of the continent. The subsidence and associated sediment supply history has impact on the later deposition of coaly deltas, and the accumulation of overburden and thermal maturity of buried sediments.